Research success : a Q & A review applying critical thinking to test taking - Valencia Go, Geraldine N. (Philadelphia : F.A. Davis Company, 2016)
"From an introduction to basic research concepts through design of quantitative and qualitative studies and data collection and analysis, you'll review all aspects of nursing research and its application to real-world practice. More than 700 NCLEX-style questions (including alternate format) in the text at Davis:Plus offer test-taking tips and rationales for correct and incorrect answers. Critical thinking facilitators for every item and research study question support learning and enhance critical thinking"--
Establishing a framework for awareness and understanding of research -- Creating the foundation for evidence-based practice -- Judging the ethical and legal aspects of research -- Exploring the role of quantitative research in evidence-based practice -- Getting familiar with quantitative research studies -- Examining research problems, purposes, and hypotheses -- Searching for relevant literature -- Describing theories and conceptual frameworks and models -- Evaluating quantitative research designs -- Evaluating other types of studies and integrative processes -- Considering the characteristics of a good design -- Determining sampling plans -- Examining data collection methods -- Anayzing the properties of research instruments -- Understanding the concepts and processes in analyzing quantitative data -- Analyzing the findings in quantitative studies -- Exploring the paradigm for qualitative studies -- Understanding qualitative approaches -- Linking qualitative processes with evidence-based practice -- Comprehensive final examination
"Two books in one: Q & A course review, NCLEX exam prep"--Cover
Includes bibliographical references and index
1 13
Keywords: Critical thinking; Nursing -- Examinations, questions, etc; Nursing -- Examinations -- Study guides; Nursing -- Problems and Exercises